Community Participation in Development Planning is Driven by Leadership, Communication, and Education - Taurista, Hafni; Choiriyah, Ilmi Usrotin (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Community participation in infrastructure development planning is crucial for ensuring sustainable growth and addressing local needs. Specific Background: In Wedoroklurak Village, Candi District, Sidoarjo Regency, low levels of community engagement in planning processes have raised concerns among local authorities and scholars. Knowledge Gap: While existing literature emphasizes the importance of community involvement, there is limited research focusing on the specific factors influencing participation in rural Indonesian contexts, particularly in relation to leadership, communication, and education. Aims: This study aims to analyze the factors affecting community participation in infrastructure development planning in Wedoroklurak Village, employing a qualitative descriptive approach. Results: Data were collected through interviews, observations, and documentation from key informants, including the Village Head, village secretary, and community leaders. The findings reveal three primary factors influencing low participation: (1) effective leadership by the Village Head, characterized by openness and authenticity; (2) robust communication between the village government and the community, facilitating a platform for dialogue; and (3) the educational background of residents, which impacts their understanding of development processes. Novelty: This research highlights the interplay between these factors, contributing to the understanding of community dynamics in rural Indonesia. Implications: The results underscore the need for enhancing educational initiatives and fostering transparent communication strategies to boost community participation in development planning. By addressing these aspects, local governments can improve engagement, leading to more effective and sustainable infrastructure projects that meet the needs of the community. Highlights: Leadership encourages community involvement in development planning. Good communication enhances community feedback and engagement. Education influences participation in infrastructure development processes. Keywords: Community Participation, Infrastructure Development, Leadership, Communication, Education